A population study of respiratory rehospitalisation in very preterm infants in the first 3 years of life. (20th May 2016) - Hong, Timothy; Bolisetty, Srinivas; Bajuk, Barbara; Abdel‐Latif, Mohamed; Oei, Julee; Jaffe, Adam; Lui, Kei
Abstract : Aim: Very premature infants consume healthcare resources following discharge from neonatal intensive care units (NICU). This study aimed to evaluate the burden of respiratory related rehospitalisation within the first 3 years post discharge in very premature infants in an Australian population. Methods: Rehospitalisation of a 4‐year cohort of NICU survivors, born less than 32 weeks gestation, was derived from data linkage of three state‐wide databases including NSW Neonatal Intensive Care Units' Data Collection, Admitted Patient Data Collection and the Death Registry. Rehospitalisation diagnoses were determined by ICD‐10 AM codes. Results: Of the 2939 survivors, 525 (18%) had bronchopulmonary dysplasia (BPD) and 261 BPD infants (50%) were discharged on home oxygen. Almost two‐third (1860, 63%) of the survivors are required rehospitalisation, respiratory causes, including 394 respiratory syncytial virus (RSV)‐related, accounted for 2668 (48%) of the 5599 rehospitalisations. Significantly more home oxygen BPD survivors had respiratory (70%) and RSV‐related (22%) rehospitalisations than the BPD infants not needing home oxygen (58% and 18%, respectively), and the survivors without BPD had the lowest rates (32% and 10%, P < 0.001). Most respiratory (61%) and RSV‐related (74%) rehospitalisations occurred during the first 12 months post discharge. No RSV‐related fatality occurred. Amongst the total 17 562 hospital days, respiratory and RSV‐related admissions accounted for 10 905 (62%) and 3031 (17.2%) days. In multivariable logistic analyses, home oxygen and maternal indigenous status were independently associated with high (3 or more) respiratory and RSV rehospitalisation rates. Conclusions: Respiratory rehospitalisations are common in very premature survivors. Home oxygen and indigenous status are significant risk factors for respiratory and RSV‐related rehospitalisations.